Comparative efficacy and safety of molecular targeted agents combined with transarterial chemoembolization in the treatment of unresectable hepatocellular carcinoma: a network meta-analysis - Long, Jiaye; Chen, Baoxiang; Liu, Zhaohui (Frontiers in Oncology, 2023)
Objective: At present, several molecular targeted agents(MTAs) combined with transarterial chemoembolization (TACE) have been employed to treat unresectable hepatocellular carcinoma (HCC). In this meta-analysis, we compared the efficacy and safety of different MTAs combined with TACE to enable effective decision-making for the clinical treatment of unresectable HCC. Methods: Pubmed, Web of Science, EMBASE, and Cochrane Library were retrieved to evaluate the efficacy and safety of different MTAs combined with TACE in cohort studies and randomized controlled trials. The hazard ratios and 95% confidence intervals (CIs) were calculated to investigate the impact of various therapies on overall survival (OS) and progression-free survival. However, the objective response rate (ORR), disease control rate (DCR), adverse events (AEs), and ≥grade-3 adverse events (≥G3-AEs) were calculated using odd ratios and 95% CIs. The node-splitting approach was used to test the heterogeneity. The funnel plot was utilized to analyze the publication bias. Additionally, according to the ranking plots, we ranked various treatments. Results: A total of 45 studies involving 10,774 patients with 8 treatment strategies were included in our network meta-analysis. Our network meta-analysis showed that apatinib+TACE provided the highest OS (62.2%), ORR (44.7%), and DCR (45.6%) , while and lenvatinib+TACE offered the best PFS (78.9%). Besides, there was no statistically significant difference in AEs and ≥G3-AEs among treatment options. Conclusion: Apatinib+TACE demonstrated the best OS, ORR, and DCR with no additional AEs and ≥G3-AEs. Therefore, for the treatment scheme of MTAs combined with TACE, apatinib+TACE may be the best option for patients with unresectable HCC. Systematic Review Registration: [https://www.crd.york.ac.uk/PROSPERO/], PROSPERO (CRD42023388609).